Study on brain damage patterns of COVID-19 patients based on EEG signals - Yao, Yang; Liu, Yingnan; Chang, Yu; Geng, Zihan; Liu, Xingting; Ma, Songnan; Wang, Zhiyun; Zheng, Chenguang; Yang, Jiajia; Ming, Dong (Frontiers in Human Neuroscience, 2023)
Objective The coronavirus disease 2019 (COVID-19) is an acute respiratory infectious disease caused by the SARA-CoV-2, characterized by high infectivity and incidence. Clinical data indicates that COVID-19 significantly damages patients' perception, motor function, and cognitive function. However, the electrophysiological mechanism by which the disease affects the patient's nervous system is not yet clear. Our aim is to investigate the abnormal levels of brain activity and changes in brain functional connectivity network in patients with COVID-19. Methods We compared and analyzed electroencephalography signal sample entropy, energy spectrum, and brain network characteristic parameters in the delta (1-4Hz), theta (4-8Hz), alpha (8-13Hz), and beta (13-30Hz) bands of 15 patients with COVID-19 and 15 healthy controls at rest. Results At rest, energy values of the four frequency bands in the frontal and temporal lobes of COVID-19 patients were significantly reduced. At the same time, the sample entropy value of the delta band in COVID-19 patients was significantly increased, while the value of the beta band was significantly decreased. However, the average value of the directed transfer function of patients did not show any abnormalities under the four frequency bands. Furthermore, node degree in the temporal lobe of patients was significantly increased, while the input degree of the frontal and temporal lobes was significantly decreased, and the output degree of the frontal and occipital lobes was significantly increased. Conclusion The level of brain activity in COVID-19 patients at rest is reduced, and the brain functional network undergoes a rearrangement. These results preliminarily demonstrate that COVID-19 patients exhibit certain brain abnormalities during rest, it is feasible to explore the neurophysiological mechanism of COVID-19's impact on the nervous system by using EEG signals, which can provide a certain technical basis for the subsequent diagnosis and evaluation of COVID-19 using artificial intelligence and the prevention of brain nervous system diseases after COVID-19 infection.